Effect of alloxan diabetes and adrenalectomy on carrageenin-induced pleurisy in the rat. - Moraes, F. R. [UNESP]; Bechara, G. H. [UNESP]; Moraes, J. R. [UNESP] (My University, 1987)
1. The effect of alloxan diabetes and adrenalectomy on the acute inflammatory response was investigated in rats using the carrageenin-induced pleurisy model. 2. Diabetic rats had reduced exudate volume (-85%) and inflammatory cell accumulation (-50%), especially polymorphonuclear leucocytes (-60%) in the pleural cavity 24 h after stimulation in relation to control values. Subcutaneous insulin administration 2 h after the inflammatory stimulus restored these parameters to normal levels. In contrast, all three measures of the response were potentiated 1.5 to 4-fold in adrenalectomized animals. 3. Results obtained by other investigators using different experimental models point to a possible pro-inflammatory function of insulin for the vascular component of inflammation. The present data show that insulin also has a significant effect on the cellular component of inflammation, especially the polymorphonuclear one, by increasing its accumulation at the affected site.